2017
DOI: 10.1016/j.jmb.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

TREM2-Ligand Interactions in Health and Disease

Abstract: The protein Triggering receptor expressed on myeloid cells-2 (TREM2) is an immunomodulatory receptor with a central role in myeloid cell activation and survival. In recent years, the importance of TREM2 has been highlighted by the identification of coding variants that increase risk for Alzheimer’s disease and other neurodegenerative diseases. Animal studies have further shown the importance of TREM2 in neurodegenerative and other inflammatory disease models including chronic obstructive pulmonary disease, mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
166
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(178 citation statements)
references
References 159 publications
(265 reference statements)
2
166
0
Order By: Relevance
“…Expression of TREM2 was noted at the time to be present on macrophages and dendritic cells but not monocytes or granulocytes (Bouchon, Dietrich, & Colonna, ). In the brain, TREM2 is expressed in microglia and perivascular macrophages but not in neurons and other brain cell types (Kober & Brett, ). Protein expression of TREM2 is low in resting microglia but is highly up‐regulated in microglia surrounding amyloid plaques in AD brains and also appears to be high in infiltrating macrophages at early cerebral infarcts (Fahrenhold et al, ; Lue et al, ).…”
Section: Trem2mentioning
confidence: 99%
“…Expression of TREM2 was noted at the time to be present on macrophages and dendritic cells but not monocytes or granulocytes (Bouchon, Dietrich, & Colonna, ). In the brain, TREM2 is expressed in microglia and perivascular macrophages but not in neurons and other brain cell types (Kober & Brett, ). Protein expression of TREM2 is low in resting microglia but is highly up‐regulated in microglia surrounding amyloid plaques in AD brains and also appears to be high in infiltrating macrophages at early cerebral infarcts (Fahrenhold et al, ; Lue et al, ).…”
Section: Trem2mentioning
confidence: 99%
“…As a most prevalent explanation of this multifaceted TREM2 signaling, a model of activating versus tonic receptor engagement by multivalent, high‐affinity versus monovalent, low‐affinity ligands is considered (Fig. ) …”
Section: Trem2mentioning
confidence: 99%
“…In 2003, Gram‐positive and Gram‐negative bacteria, such as Escherichia coli , Staphylococcus aureus , Proteus mirabilis and Streptococcus pyogenes ; fungus, such as Candida guilliermondii ; and an astrocytoma cell line, as well as polyanionic molecules, were identified as TREM2 ligands . Furthermore, it has been reported that TREM2 can bind to various cells and cell‐derived molecules, such as apoptotic neuronal cells; anionic molecules derived from apoptotic cells, such as phosphatidylethanolamine, phosphatidylserine (PS) and cardiolipin; heat shock protein 60; and apolipoprotein (Apo) including ApoE . Among the various identified TREM2 ligands, the affinity between TREM2 and phosphatidylserine is very high, whereas the affinity between TREM2 and heat shock protein 60 is very low (Fig.…”
Section: Trem2 Ligandsmentioning
confidence: 99%
“…TREM2 is exclusively expressed on myeloid lineage cells including dendritic cells, tissue macrophages, osteoclasts, and microglia [11,12]. Many potential ligands for TREM2 have been proposed, which are characterized based on the type of anionic and/or lipidic species, such as bacterial components, mammalian cellular membrane components and lipoproteins [15]. TREM2 interacts with the adaptor protein DNAX-activating protein 12 (DAP12)/TYRO protein kinase binding protein (TYROBP) via its transmembrane domain.…”
Section: Structure Function and Features Of Trem2mentioning
confidence: 99%
“…Additionally, the function of sTREM2 has not been elucidated, although elevated sTREM2 levels in CSF have been suggested to reflect microglial activation in response to neuronal degeneration [27][28][29][30][31]. In this respect, recent studies uncovered sTREM2 as not just an inactive end-product but also a signaling molecule [15] that promotes macrophage survival by preventing apoptosis [32] and activates microglia to ultimately trigger inflammatory responses and prolong survival [33]. These findings hint at the pathological implications of sTREM2 in chronic inflammation, and further elucidation of the pathophysiological roles of CSF and blood sTREM2 will provide significant novel clues on the regulation of central and systemic inflammation by targeting sTREM2 and/or sTREM2-related processes such as proteolytic production.…”
Section: Emerging Implications Of Trem2 and Strem2 In Neurodegeneratimentioning
confidence: 99%